2013
DOI: 10.1002/bjs.9025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic and open intraoperative ultrasonography for staging liver tumours

Abstract: Laparoscopic IOUS is a reliable tool for staging liver tumours with a performance similar to that of open IOUS in detecting new nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…It is known that open intraoperative liver ultrasound represents an indispensable tool for staging of hepatobiliary cancers [9,10]. Our previous study [20] demonstrated that laparoscopic ultrasound, despite technically demanding, has the same performance of open intraoperative ultrasound in staging liver diseases, especially in detecting new nodules. In fact, one quarter of patients were defined as unresectable only thanks to ultrasound findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that open intraoperative liver ultrasound represents an indispensable tool for staging of hepatobiliary cancers [9,10]. Our previous study [20] demonstrated that laparoscopic ultrasound, despite technically demanding, has the same performance of open intraoperative ultrasound in staging liver diseases, especially in detecting new nodules. In fact, one quarter of patients were defined as unresectable only thanks to ultrasound findings.…”
Section: Discussionmentioning
confidence: 99%
“…Any suspected lesion was biopsied and sent for frozen section analysis. A similar technique was used for both open and laparoscopic liver ultrasound as previously described [20]: Two consecutive liver explorations were done, the first to evaluate liver anatomy and the second one for identification and characterization of known lesions and exploration of all liver segments from left lateral to the right posterior segments, including segment 1. ProSound Alpha 5sv or ProSound Alpha 7 ultrasound system (Hitachi Aloka Medical, Tokyo, Japan) was used.…”
Section: Patients Managementmentioning
confidence: 99%
“…The reliability of LUS for staging liver diseases was demonstrated by its performances similar to those of open IOUS [8]. Furthermore, it has to provide real-time guidance during surgery.…”
mentioning
confidence: 93%
“…Un pilar fundamental y transversal a todos los cirujanos y patologías (especialmente las malignas) es el uso de la ecografía intraoperatoria laparoscópica (EIOL). Esta es esencial a la hora de planificar el abordaje de la lesión en varios aspectos, partiendo por la adecuada visualización de los bordes en resecciones no anatómicas y anatómicas para así lograr el margen adecuado, etapificarla correctamente al descartar la presencia de lesiones satélites no pesquisadas en las imágenes preoperatorias y como guía imprescindible a la hora de planificar la transección del parénquima ayudando en la identificación de las estructuras importantes a respetar o seccionar, tales como las venas suprahepáticas y los pedículos portales más importantes 3 . La EIOL pasa a ser la extensión de las manos del cirujano y viene a reemplazar la necesidad de la palpación del hígado, por lo cual debe estar siempre disponible a la hora de realizar una resección hepática laparoscó-pica (RHL).…”
Section: Introductionunclassified